Comparison of Two Commercial ELISAs against an In‐House ELISA for Measuring Soluble CD26 in Human Serum - Ohnuma, Kei (J Clin Lab Anal, 2014)
BACKGROUND: CD26 is a T‐cell costimulatory molecule with dipeptidyl peptidase IV (DPPIV) activity in its extracellular region. The relevance of sCD26 levels and disease activity has been reported in rheumatic or infectious disease. For certain metabolic and endocrine conditions, DPPIV inhibitors were recently developed as a new class of antidiabetic drugs that act by inhibiting DPPIV, the enzyme that inactivates incretin hormone. Higher levels of sCD26 in diabetic patients have been shown to be associated with a poor clinical response to DPPIV inhibitors, with sCD26/DPPIV being an adipokine that may impair insulin sensitivity. With the increasing use of serum sCD26 and DPPIV enzyme activity as biomarkers with potential clinical implications, accurate measurements of serum sCD26 levels and DPPIV enzyme activity are needed. METHODS: We compare two commercially widely available and an in‐house enzyme‐linked immunosorbent assays (ELISAs) for measurement of serum sCD26 in healthy or diabetic human sera. RESULTS: The significant discrepancies among the results obtained from commercially available and the in‐house sCD26 assays were found. We also observed that a linear correlation between serum sCD26 level and DPPIV enzyme activity exists with the in‐house ELISA, while the commercial ELISAs demonstrate a lack of consistency between serum sCD26 level and DPPIV enzyme activity. CONCLUSION: These data strongly suggest that new commercial assays for sCD26 plasma levels need detailed evaluation and validation with samples from clinically well‐characterized patients, and results obtained from these newer assays should be compared to those obtained from well‐established in‐house assays such as our assay or other validated sCD26 ELISA assays.